Stardust from meteorites : an introduction to presolar grains - Lugaro, Maria (World Scientific series in astronomy and astrophysics ;, 2005)
The study of presolar meteoritic grains is a new inter-disciplinary field that brings together topics from nuclear physics to astronomy and chemistry. Traditionally, most of the information about the cosmos has been gathered by observing light through telescopes. However, with the recent discovery that some dust grains extracted from primitive meteorites were produced in stellar environments, we now have the opportunity to gather information about stars and our Galaxy from the laboratory analysis of tiny pieces of stardust. Stellar grains represent a unique and fascinating subject of study. Th.